Analisis Permasalahan Pembelajaran Pendidikan Pancasila dan Kewarganegaraan pada Siswa (Lembaga Pengembangan Kinerja Dosen, 2026)
Problems in learning Pancasila and Citizenship Education (PPKn) for students are caused by various factors, including school factors, teachers, and the students themselves. The purpose of this study is to identify and understand in depth the problems that occur and determine the steps that can be taken to overcome these problems. This study uses a descriptive approach with qualitative methods. The main instrument in this study is the researcher herself, who is tasked with determining the research focus, collecting, analyzing, and interpreting data, and drawing conclusions based on field findings. Data collection techniques used are observation, in-depth interviews, and documentation. Informants in this study include the principal, PPKn teachers, and students at the UPTD SMP Negeri 7 Mandrehe. The results of the study indicate that the main problems in PPKn learning are caused by low student interest and motivation, the use of monotonous learning methods by teachers, limited learning media, and minimal supporting facilities and infrastructure at the school. These conditions have an impact on students' lack of understanding of the values of Pancasila and citizenship. To address this issue, various efforts have been made, including requiring teachers to use more varied, innovative, and enjoyable learning methods. Furthermore, schools are expected to provide support by organizing teacher training and providing learning facilities and infrastructure, such as libraries, audio-visual media, and classrooms that support active and interactive teaching and learning activities. These steps are expected to make PPKn learning more effective and beneficial for students. Problems in Pancasila and Citizenship Education (PPKn) learning for students are caused by various factors, including school, teacher, and student factors. The purpose of this study is to identify and understand in-depth the problems that occur and determine steps that can be taken to address these issues.